GDSL esterase/lipases OsGELP34 and OsGELP110/OsGELP115 are essential for rice pollen development. Issue 10 (24th March 2020) - Zhang, Huihui; Wang, Menglong; Li, Yiqi; Yan, Wei; Chang, Zhenyi; Ni, Haoling; Chen, Zhufeng; Wu, Jianxin; Xu, Chunjue; Deng, Xing Wang; Tang, Xiaoyan
Abstract: Pollen exine contains complex biopolymers of aliphatic lipids and phenolics. Abnormal development of pollen exine often leads to plant sterility. Molecular mechanisms regulating exine formation have been studied extensively but remain ambiguous. Here we report the analyses of three GDSL esterase/lipase protein genes, OsGELP34, OsGELP110, and OsGELP115, for rice exine formation. OsGELP34 was identified by cloning of a male sterile mutant gene. OsGELP34 encodes an endoplasmic reticulum protein and was mainly expressed in anthers during pollen exine formation. osgelp34 mutant displayed abnormal exine and altered expression of a number of key genes required for pollen development. OsGELP110 was previously identified as a gene differentially expressed in meiotic anthers. OsGELP110 was most homologous to OsGELP115, and the two genes showed similar gene expression patterns. Both OsGELP110 and OsGELP115 proteins were localized in peroxisomes. Individual knockout of OsGELP110 and OsGELP115 did not affect the plant fertility, but double knockout of both genes altered the exine structure and rendered the plant male sterile. OsGELP34 is distant from OsGELP110 and OsGELP115 in sequence, and osgelp34 and osgelp110/osgelp115 mutants were different in anther morphology despite both were male sterile. These results suggested that OsGELP34 and OsGELP110/OsGELP115 catalyze different compounds for pollen exine development. Abstract : Abnormal development of pollen exine often leads to plant sterility. Here we report the identification of three GDSL esterase/lipase protein genes, OsGELP34 and the redundant OsGELP110 and OsGELP115 genes, which are required for rice pollen fertility. OsGELP34 and OsGELP110/OsGELP115 regulate exine formation through different mechanisms.